Circadian Clock-Controlled Checkpoints in the Pathogenesis of Complex Disease - Li, Min-Dian; Xin, Haoran; Yuan, Yinglin; Yang, Xinqing; Li, Hongli; Tian, Dingyuan; Zhang, Hua; Zhang, Zhihui; Han, Ting-Li; Chen, Qing; Duan, Guangyou; Ju, Dapeng; et al. (Frontiers in Genetics, 2021)
The circadian clock coordinates physiology, metabolism, and behavior with the 24-hour cycles of environmental light. Fundamental mechanisms of how the circadian clock regulates organ physiology and metabolism have been elucidated at a rapid speed in the past two decades. Here we review circadian networks in more than six organ systems associated with complex disease, which cluster around metabolic disorders, and seek to propose critical regulatory molecules controlled by the circadian clock (named clock-controlled checkpoints) in the pathogenesis of complex disease. These include clock-controlled checkpoints such as circadian nuclear receptors in liver and muscle tissues, chemokines and adhesion molecules in the vasculature. Although the progress is encouraging, many gaps in the mechanisms remain unaddressed. Future studies should focus on devising time-dependent strategies for drug delivery and engagement in well-characterized organs such as the liver, and elucidating fundamental circadian biology in so far less characterized organ systems, including the heart, blood, peripheral neurons, and reproductive systems.